On a New Conformal Euler-Lagrangian Equations on Para-Quaternionic Manifolds (Global Journal of Science Frontier Research, 2020)
In this paper we obtain Euler-Lagrange equations for quantum and classical mechanics by means of a canonical local basis {ð‘ð‘, ð‘®ð‘®} of V that they defined on a generalized quaternionic ð‘²ð‘²ð’‚ð’‚Ìˆð’‰ð’‰ð’‰ð’‰ð’‰ð’‰ð’‰ð’‰ manifold (M, g, V).